Impacts of the Madden-Julian oscillation on intraseasonal precipitation over northeast Brazil - Valadão, Cati Elisa de Avila (2015)
The impacts of the Madden–Julian Oscillation (MJO) on precipitation over Northeast Brazil (NEB, also known as Nordeste) are evaluated based on daily raingauge data from 492 stations over 30-year period (1981-2010). Composites of precipitation, outgoing longwave radiation and moisture-flux anomalies are performed for each phase of the MJO based on the Jones–Carvalho MJO index. To distinguish the MJO signal from other patterns of climate variability, daily data are filtered using a 20 - 90 day band-pass filter; only days classified as MJO events are considered in the composites. A preliminary analysis based on precipitation data was conducted for a small scale area located in NEB’s semiarid interior, in an area known as Seridó. The Seridó is one of the driest regions in NEB, and is recognized by the United Nations Convention to Combat Desertification as particularly vulnerable to desertification. Composites of rainfall anomalies were computed for each of the eight phases of the MJO during February-May, which is Seridó’s main rainy season. Results showed that the rainfall patterns in Seridó undergo substantial changes (from enhancement to suppression) as the convective center of the MJO propagates eastward. When combining the MJO signals for wet and dry phases, the difference represents about 50 - 150% modulation of the mean rainfall over Seridó. Then a comprehensive analysis of the role of the MJO in modulating the spatiotemporal variation of NEB’s precipitation was performed, considering all four seasons. The results showed strong seasonality of the MJO impact on precipitation. The most spatially coherent signals of precipitation anomalies occurred in the austral summer, when about 80% of the raingauge stations showed increased precipitation during phases 1 - 2 and suppressed precipitation in phases 5 - 6 of the oscillation. Although the MJO impacts precipitation on intraseasonal timescales in all seasons in most locations, these impacts vary in magnitude and depend on the phase of the oscillation. Precipitation anomalies over NEB are explained by the interaction of convectively coupled Kelvin-Rossby waves with the dominant climatic features in each season. During the austral summer and spring, westerly regimes increased precipitation over most NEB. In the austral winter and fall, precipitation anomalies exhibited more complex spatial variability. In these seasons precipitation anomalies in eastern coastal areas depended on the strength of the South Atlantic anticyclone, which is largely modulated by Rossby waves. The strengthening of the anticyclone intensified the convergence of the trade winds in coastal areas and precipitation windward of the coastal range. Conversely, the intensification of the subsidence was responsible for precipitation deficits in the lee side of the range. These conditions were typically observed when easterly regimes dominate over tropical South America and NEB, decreasing moisture flow from the Amazon.